MARGIN PEMASARAN TOMAT APEL DI KELURAHAN KOLONGAN BEHA BARU KECAMATAN TAHUNA BARAT - Musperi Menggasa; Mex F.L. Sondakh; Grace A.J. Rumagit; Oktavianus Porajouw (Universitas Sam Ratulangi, 2014)
ABSTRACTMusperi Menggasa. Marketing Margin of Tomato (Lycopercicumpryformer) in Kolongan BehaBaru andVillage, West Tahuna sub District. Under Guidance of MF. Sondakh as a Chairman, Grace A. J. Rumagit, O. Porajouw as members.The Objective of this research is to study the marketing margin of tomato (Lycopercicumpryformer) in Sangihe Regency. This study uses a purposive sampling method and then sampling from the farmers is traced to marketing agencies of tomato by using snow ball sampling method. This study is analyzed descriptively by calculating the magnitude of each channel marketing margin and profit margin.The result of this research showed that marketing agenciesin Kolongan Beha Baru Village consisted of Farmers, Retailers, collecting trader and Consumers. Marketing channels freely selectable means direct marketing agencies can choose which marketing channels are more profitable. While the marketing channel is Zero Level channel (Farmer-Consumer), Level One Channel (Farmer-Retailer-Consumer) and Level Two Channel (Farmer-Collecting Traders- Retailer-Consumer).Tomatoes marketing margins in Kolongan Beha Baru Village Channel Level I was Rp. 333.3,- with an average profit margin earned by each marketing agencies was 12.5 with a selling price at the retail level is the purchase price at the consumer level. The average value of marketing margin of tomato in Kolongan Beha Baru in Channel Level II was Rp. 4.833.3, - with an average profit margin earned by each agency marketing was Rp. 1.701.6 . The low value of the profit margin was affected by the value of marketing costs. Thus the best marketing channels was level one channel.